Increased bone turnover, osteoporosis, progressive tibial bowing, fractures, and scoliosis in a patient with a final‐exon SATB2 frameshift mutation. Issue 11 (13th July 2016) - Boone, Philip M.; Chan, Yiu Man; Hunter, Jill V.; Pottkotter, Louis E.; Davino, Nelson A.; Yang, Yaping; Beuten, Joke; Bacino, Carlos A.
Abstract : Haploinsufficiency of SATB2 causes cleft palate, intellectual disability with deficient speech, facial and dental abnormalities, and other variable features known collectively as SATB2 ‐associated syndrome. This phenotype was accompanied by osteoporosis, fractures, and tibial bowing in two previously reported adult patients; each possessed SATB2 mutations either predicted or demonstrated to escape nonsense‐mediated decay, suggesting that the additional bone defects result from a dominant negative effect and/or age‐dependent penetrance. These hypotheses remain to be confirmed, as do the specific downstream defects causing bone abnormalities. We report a SATB2 mutation (c.2018dupA; p.(H673fs)) in a 15‐year‐old patient whose SATB2 ‐associated syndrome phenotype is accompanied by osteoporosis, fractures, progressive tibial bowing, and scoliosis. As this homeodomain‐disrupting and predicted truncating mutation resides within the final exon of SATB2, escape from nonsense‐mediated decay is likely. Thus, we provide further evidence of bone phenotypes beyond those typically associated with SATB2 ‐associated syndrome in individuals with potential dominant‐negative SATB2 alleles, as well as evidence for age‐dependence of bone features. Elevations in alkaline phosphatase, urinary N‐telopeptide/creatinine ratio, and osteocalcin in the patient indicate increased bone turnover. We propose surveillance and treatment with osteoclast inhibitors to prevent fractures and to slow progressive bone deformities. © 2016 Wiley Periodicals, Inc.